Implementation of an Eco-Hydrological Classification in Chilean Rivers [Implementación de Una Clasificación Eco-Hidrológica Para Los Ríos de Chile] - Quevedo-Tejada, D (Universidad de Concepcion, 2011)
Concern has grown in Chile to protect and conserve aquatic ecosystems taking into account the high degree of habitat degradation. As a first step towards the development of conservation plans, it is necessary to classify these ecosystems in order to learn about them and understand their different types and functions. Considering that hydrological regime is the main factor in the composition of river ecosystems, an Eco-Hydrological Classification of Chilean Rivers (REC-Chile) has been developed. REC-Chile is based on the hierarchical superposition of the controlling factors of the hydrological pattern in Chile. REC-Chile is a multi-scale classification system, allowing to represent different river patterns at different spatial scales according to the selected controlling factors. The typology of the river segment is represented as a 6-digit code, in which the position of the digit represents the controlling factor and the digit value represents the factor category. This hierarchical configuration and the assignment of geography- independent classes makes REC-Chile an easy way of interpreting the hydrological classes. Given the fl exibility provided by the multi-scale nature of REC-Chile, and the simplicity in the interpretation f the classes, it is expected that REC-Chile will become a very useful and suitable tool for developing conservation plans for aquatic ecosystems.
Keywords: Hierarchical classification; controlling factors; hydrological pattern; rivers; Chile